2021
DOI: 10.1007/s12152-021-09474-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroparenting: the Myths and the Benefits. An Ethical Systematic Review

Abstract: Parenting books and early childhood policy documents increasingly refer to neuroscience to support their parenting advice. This trend, called ‘neuroparenting’ has been subject to a growing body of sociological and ethical critical examination. The aim of this paper is to review this critical literature on neuroparenting. We identify three main arguments: that there is a gap between neuroscientific findings and neuroparenting advice, that there is an implicit normativity in the translation from neuroscience to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Therefore, the field of neuroscientific research may require neuroscience communication specialists, as suggested by Dekker et al [2012]. A recent investigation by Snoek and Horstkötter [2021] shows that there is still a gap between (neuro)science and its applicability to parenting practices. When translating (neuro)scientific findings to practical advice, they suggest that not only policy makers and media, but also parents themselves should critically examine the findings and should be encouraged to examine their own, often implicit ideas about neuroscientific findings.…”
Section: Parents' Understanding Of Neuroscientific Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the field of neuroscientific research may require neuroscience communication specialists, as suggested by Dekker et al [2012]. A recent investigation by Snoek and Horstkötter [2021] shows that there is still a gap between (neuro)science and its applicability to parenting practices. When translating (neuro)scientific findings to practical advice, they suggest that not only policy makers and media, but also parents themselves should critically examine the findings and should be encouraged to examine their own, often implicit ideas about neuroscientific findings.…”
Section: Parents' Understanding Of Neuroscientific Informationmentioning
confidence: 99%
“…The results show that even though parents might have negative views on adolescent brain development, they still understand their children's behaviours and their negative views seem not to be reflected in their self-reported parenting behaviours. A better understanding of the adolescent brain may help parents to understand the behaviour of their adolescents and help them even to implicitly develop new parenting skills [Snoek & Horstkötter, 2021] with high levels of support and low levels of controlling behaviours. Additionally, these low levels of controlling behaviours of parents could also be explained by a unique characteristic of adolescence; the adolescents' increasing demand for more autonomy.…”
Section: Impact Of Neuroscientific Communicationmentioning
confidence: 99%